THU0032 Involvement of ER stress signals, PERK, IRE1, GRP78 in rankl-induced, C-FOS and NFATC1-mediated osteoclastogenesis. (23rd January 2014) - Yoo, W.-H.; Lee, E.-G.; Sung, M.-S.; Hong, M.J.; Hong, Y.K.; Lee, C.-H.; Lee, M.S.
Abstract : Background: ER stress has an important role in the pathogenesis of bone and cartilage destruction in inflammatory conditions, such as RA. However, there were no studies about relations ER stress-specific signals and RANKL-mediated signaling pathways. Objectives: To investigate the effects of thapsigargin (TG)-induced ER (Endoplasmic Reticulum) stress and chemical chaperone, 4-phenylbutyric acid (PBA) on the RANKL-induced, c-Fos and NFATc1-mediated osteoclastogenesis and its mechanisms. Methods: Bone marrow cells (BMCs) were obtained from tibia and femur of 5-week-old male imprinting control region (ICR) mice and cultured with M-CSF and RANKL with or without TG, IL-1β, and PBA. mRNA in BMCs transfected with dummy small interfering RNA (SiRNA) or GRP78, PERK and IRE1 SiRNA were profiled using microarray technology. The formation of osteosclasts was evaluated with TRAP staining and resorption pit assay with dentine slice. The expression of ERK 1/2, p-ERK, c-Jun amino-terminal kinase (JNK), p-JNK, p38, p-p38, NF-κB (p65), c-Fos, NFATc1 and ER stress signals, including eIF2α, GRP78, PERK and IRE1 were examined by RT-PCR and immunoblotting. Results: IL-1β and TG-induced ER stress increased the formation of osteoclasts, which was inhibited by PBA. IL-1β and/or TG-induced osteoclastogenesis was mediated with osteoclast specific signals, including c-Fos, NFATc1 and ER stress associated signaling pathways, PERK, IRE1, GRP78, eIF2α which were downregulated with PBA. Knockdown of the ER stress signals, including PERK, IRE1 and GRP78 by SiRNA inhibited osteoclast-specific signals such as NFATc1 and c-Fos, and thus inhibited IL-1β and/or TG-induced formation of osteoclasts. Conclusions: ER stress increased the c-Fos and NFATc1-mediated osteoclastogenesis via upregulation of eIF2α, GRP78, PERK and IRE1, and which was inhibited by ER stress inhibitor, PBA. These results suggest that modulation of the mechanisms of ER stress in osteoclast differentiation might be a new therapeutic target to prevent inflammatory and destructive arthritic disease such as RA and diverse osteoporosis. References: Takayangi H. New immune connections in osteoclast formation. Ann NY Acad Sci 2010;1192:117-123. Hotamisligil GS. Endoplasmic reticulum stress and the inflammatory basis of metabolic disease. Cell 2010;140:900-17. Yip KH, Zheng MH, Steer JH, Giardina TM, Han R, Lo SZ, Bakker AJ, Cassady AI, Joyce DA, Xu J. Thapsigargin modulates osteoclastogenesis through the regulation of RANKL-induced signaling pathways and reactive oxygen species production. J Bone Miner Res. 2005;20(8):1462-71. Disclosure of Interest: None Declared